Sie sind auf Seite 1von 4

·, · ||v|| 2 = v, v

||v + w|| 2 + ||v w|| 2 = v + w, v + w + v w, v w

= v, v + 2 v, w + w, w + v, v 2 v, w + w, w

= 2||v|| 2 + 2||w|| 2 .

(V, || · ||)

v, w :=

2 1 ||v + w|| 2 − ||v|| 2 − ||w|| 2

v, v =

2 1 ||2v|| 2 2||v|| 2 = ||v|| 2 .

v 1 , v 2 , w V

||v 1 + v 2 + w|| 2

= 1

2 ||(w + v 1 ) + v 2 || 2 + ||(w + v 2 ) + v 1 || 2

= + ||v 2 || 2 2 ||w + v 1 v 2 || 2 + ||w + v 2 || 2 + ||v 1 || 2 2 ||w + v 2 v 1 || 2

||w + v 1 || 2

1

1

= + ||w + v 2 || 2 + ||v 1 || 2 + ||v 2 || 2 − ||v 1 v 2 || 2 − ||w|| 2

||w + v 1 || 2

v 1 + v 2 , w =

=

=

=

=

2 1 ||v 1 + v 2 + w|| 2 − ||v 1 + v 2 || 2 − ||w|| 2

||(w + v 1 )|| 2

||(w + v 1 )|| 2

1 + ||(w + v 2 )|| 2 + ||v 1 || 2 + ||v 2 || 2 − ||v 1 v 2 || 2 − ||v 1 + v 2 || 2 2||w|| 2

2

1 + ||(w

2

2 1 ||v 1 + w|| 2 − ||v 1 || 2 − ||w|| 2 + 1

v 1 , w + v 2 , w

+

v 2 )|| 2 − ||v 1 || 2 − ||v 2 || 2 2||w|| 2

2 ||v 1 + w|| 2 − ||v 1 || 2 − ||w|| 2

v, w V α R

αv, w = α v, w .

α = n N

nv, w = v + (n 1)v, w = v, w + (n 1)v, w = v, w + (n 1) v, w = n v, w

k = n n N

0 = 0v, w = nv + (n)v, w = nv, w + (n)v, w = n v, w + (n)v, w

kv, w = k v, w α = p

q

Q

q p v, w = q · p v, w = pv, w = p v, w

q

q

q p v, w = p v, w α R α n Q α n α n → ∞ V

| ||α n v + w|| − ||αv + w|| | ≤ |α α n | · ||v||

q

q

αv, w =

n α n v, w = lim

lim

n α n v, w = α v, w .

E 1 , E 2 , E 3 R 3 R 3

0

1

0

a

a

a

1

2

3

= a 1

1

0

0

+ a 2

+ a 3

0

0

1

=

3

i=1

a i E i .

3

i,j,k=1

 (a × b) × c = 3 a, c b − b, c a = j=1 3 = i,j=1 3 =

a i b j c k (E i × E j ) × E k

3

i=1

b, c a i E i

3

a i b j c j E i

a, c b j E j

a i c i b j E j

i,j=1

a i b j c k ( E i , E k E j E j , E k E i ).

i,j,k=1

1 i, j, k 3 i = j 0

E i × E j = ±E k ±E k × E k = 0 0 (1) E i E j

E 2 × E 3 = E 1 ,

(E i × E j ) × E k = E i , E k E j E j , E k E i

E 1 × E 2 = E 3 ,

E 3 × E 1 = E 2 .

i

= j = k

E i

 (E 1 × E 2 ) × E 2 = E 3 × E 2 = −E 1 , (E 1 × E 3 ) × E 3 = −E 2 × E 3 = −E 1 (E 2 × E 3 ) × E 3 = E 1 × E 3 = −E 2 , (E 2 × E 1 ) × E 1 = −E 3 × E 1 = −E 2

(E 3 × E 1 ) × E 1 = E 2 × E 1 = E 3 ,

(E 3 × E 2 ) × E 2 = E 1 × E 2 = E 3

z, z =

n

k=1

z¯ k z k =

n

k=1

|z k | 2 .

z, w = w, z .

z, z , w, w C n α, β C

 ¯ αz + βz , w = α¯ z, w + β z, w z, αw + βw = α z, w + β z, w

z, w C α C

0 ≤ ||z αw|| 2 = ||z|| 2

α z, w α |α| 2 ||w|| 2 α w, z

= ||z|| 2 + |α| 2 ||w|| 2 2 (α z, w ).

α = w, z /||w|| 2

0 ≤ ||z|| 2 | z, w | 2

||w|| 2

| z, w | ≤ ||z|| · ||w||

x 0 E a a x 0 a x 0 ν a x 0 = λν x 0 = a λν x 0 E

0 = x 0 , ν = a λν, ν = a, ν λ ν, ν

x 0 := a a, ν

||ν|| 2

ν.

λ = a, ν

||ν|| 2 .

x 0 x E x = x 0 + (x x 0 )

||a x|| 2 = ||(a x 0 ) + (x 0 x)|| 2 = ||a x 0 || 2 + ||x 0 x|| 2 + 2 a x 0 , x 0 x .

x 0 x E

a x 0 = λν

E

a x 0 , x 0 x = 0

||a x|| 2 = ||a x 0 || 2 + ||x 0 x|| 2 ≥ ||a x 0 || 2

x = x 0

d(a, E) = ||a x 0 || = | a, ν |

||ν||

.

lim

n→∞

n 2 + 5n

=

3n 2 2

lim

n→∞

1
+ 5 1
1 + 0
1
n
3
− 2
= − 0 = 3
3
n 2

|a n a n+1 | = 2n + 1

2
2
0 ≤ a n = √ n + 1 − √ n − 1 =
√ n + 1 + √ n − 1 ≤
√ n + 1

n → ∞ 0 a n 0

lim

n→∞

1

2

n n

k

=

=

=

=

lim

n→∞

n(n 1) · · · (n k + 1) 1 · 2 ··· k

1

2

n

lim

n→∞

1 · n1

n

··· nk+1

n

· n k

2

n

k!

lim

n→∞

1 1

n ··· 1 k1 k!

1

n

k!

1

lim

n→∞

n

k

2

n

= 0

lim

n→∞

n

k

2

n

3+4

5

= 1

|a n+1 a n | =

3 + 4 n 3 + 4

5

5

1 =

3 + 4

5

− 1 = 1
5 √ 20.

3 · 5

n 3 1 a n 5

5 n a n = 3 n + 4 n + 5 n

5

=

n

n

3 · 5 n =

n

n

1 a n =

7n 6 + 2n 2 + 1

n

10n 6 =

n

10 · n 6

n

n

a n 1

10

n

n n 1

n 10

2

n

0

lim

n→∞

2 n n

10

=

2 n + n 10

lim

n→∞

10
n
1
2
n
+ n 10
1
2
n

= 1.

lim n

x n =

n n 1 x n > 0 n 4

n = 1

n

n = (1 + x n ) n =

n

k=0 n

k

x

n n

3

k

x

3

n =

n 3 3n 2 + 2n

6

x

n n 3

3

6

· n 3

n

· x

n n 24 3 x

3

3

n .

x n

3 24 · n 2/3

0 a n = n · x n

24 · n 2 · n 3

3

1

2 =

24 · n 1

3

6

0 a n